1H NMR‐based metabolomics approach for understanding the fermentation behaviour of Bacillus licheniformis. Issue 3 (29th June 2015) - Yan, Zheng; Zheng, Xiao‐Wei; Han, Bei‐Zhong; Yan, Yin‐Zhuo; Zhang, Xin; Chen, Jing‐Yu
<x xml:space="preserve">Abstract</x> Bacillus licheniformis has been found to be one of the persistent dominant microorganisms in Daqu, which is a traditional fermentation starter, and it has been used to intensify certain strains. To understand the impact of B. licheniformis on Daqu, the fermentation behaviour of B. licheniformis was studied using 1H NMR‐based non‐targeted analysis and principal component analysis. During the fermentation, 53 compounds were identified. Among them, seven compounds were largely consumed and 17 metabolites were largely accumulated. The macromolecular starch and cellulose were degraded by B. licheniformis, and then utilized to produce acetic acid, lactic acid, propionic acid, succinate acid, etc. Principal component analysis was carried out to study the variations of analytes during the fermentation. Samples collected at each time point could be clearly discriminated and the biomarkers of each time point were defined. A variety of biochemical compounds (such as acetate, ethanol, lactate, pyruvate, malate, maltose and sucrose) were changed during the fermentation of B. licheniformis. The results are useful to reveal how and why B. licheniformis becomes dominant in Daqu, and to reveal its impact on the aroma formation of Daqu and its derived products. Copyright © 2015 The Institute of Brewing & Distilling